Reversible Antifertility Effect of Withaferin (Global Journal of Science Frontier Research, 2020)
Background: Currently world population crosses the 7.30 billion and increasing continuously day by day. There is a great need to support an individuals in family-planning since increasing growth rate of world's population caused negative impact on sustainable, economic growth and increased poverty especially in developing countries. However, there is still no method available in the field of male contraception that satisfies the essential criteria of safety, efficacy, economy and complete reversibility. Clearly, there is a need for development of reversible contraceptive from natural resources. Therefore, we have performed the present study to examine the effect of Withaferin-A on the sexual hormone levels and to consider the effect of alkaloid of Withania somnifera on changes of glucose, cholesterol and triglyceride serum levels in male rats and can prevent the fertility of male albino rat by evaluating some andrological parameters such as sperm motility, sperm counts, rate of fertility and morphology which are some of the indices that determine the ability of a male to produce viable spermatozoa.
Keywords: Withania somnifera; Withaferin-A; Contraceptive; Antifertility; Sperm Motility